1978
DOI: 10.1007/bf00023703
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of genetic markers from two potato dihaploids and their respective parent cultivars

Abstract: Potato. dihaploid, marker genes . SUMMARY In the first inbred generation (I,) of cv . Black 4495 a dark green, slowly growing mutant (coded ds) was found, whereas the 1, of its self-compatible dihaploid, B16, comprised this ds mutant and in addition the mutants virescens (v) and yellow margin (ym). The occurrence of ds and ym might trace back to diploid S . phureja, one of the ancestors of Black 4495 . No lethal mutants were observed in 1, of B16 . Analysis of I, of cv . Gineke revealed a simplex condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This was published for instance already by CORRENS (1919) for Caps&. More recently it was reported for potato that yellow leaf margin and variegated tuber skin are genetically controlled (HOWARD, 1970;HERMSEN et al, 1978). Some variegated ornamental plants are even seed-propagated, as are Coleus cultivars and foliage begonias, which often strikingly resemble real periclinal chimeras.…”
mentioning
confidence: 86%
“…This was published for instance already by CORRENS (1919) for Caps&. More recently it was reported for potato that yellow leaf margin and variegated tuber skin are genetically controlled (HOWARD, 1970;HERMSEN et al, 1978). Some variegated ornamental plants are even seed-propagated, as are Coleus cultivars and foliage begonias, which often strikingly resemble real periclinal chimeras.…”
mentioning
confidence: 86%
“…It must be kept in mind, that the genetical background will play an important role in such a relationship. For the material of the present study it is important to know that HERMSEN et al (1978) found three lethal genes in G254 which affect the germination rate of the seeds. Such genes might be present and segregating in the trisomic material as well, since G254 was the male parent in all original 3x x 2x crosses.…”
Section: Resultsmentioning
confidence: 99%
“…Several marker genes have already been reported in diploid potato (DODDS & LONG, 1955, 1956SIMMONDS, 1965;DE JONG & ROWE, 1972;HERMSEN et al, 1978). These developments are particularly encouraging for establishing a trisomic series in diploid S. tubcrosum.…”
Section: Introductionmentioning
confidence: 88%